Movement of Landless Rural Workers and Training for Gender Equality - Pessoa, Jeniffer Ribeiro [UNESP]; Dal Ri, Neusa Maria [UNESP] (Univ Federal Tocantins, Campus Tocantinopolis, 2017)
The Landless Rural Workers Movement (MST) was formed in 1984 with the main objective of fighting for agrarian reform in Brazil. With more than 30 years of history, the MST, in addition to organizing production and political intervention, has built an important educational work for the Landless and a formation focused on the change of values. Among these values we highlight the struggle for gender equality. Thus, the main objective of this article is to present to the readers an analysis of the MST's gender policies, highlighting the connection of this type of policy with the formation of the Landless. The procedures adopted were documentary research and bibliographic research. For the collection of data, the official MST publications, texts prepared by its members and specialized literature on the subject were used. The analysis led us to conclude that the Movement, since its inception, has produced theoretical texts and developed practical actions trying to increase the participation of women in production, decision-making bodies and political coordination; Guarantee and expand the legal rights of women; Combat violence against women; And introduce gender equality in their formal education and training courses. To this end, the MST elaborated strategic proposals and created a Gender Sector focused on the promotion of gender equality and equal participation.
Keywords: MST; Gender Equality; Education